Resolução de problemas que envolvem a multiplicação e a divisão de números naturais: um estudo das estratégias de estudantes do 5º ano - Adelaide da Silva Carvalho (2020)
This master's research presents the investigation and explanation of the strategies of a group of students in the 5th year of elementary school at a public school in Ibirité, Minas Gerais, during Problem Solving involving the multiplication and division of natural numbers. The Problem Solving situations allow, in most cases, students to make associations between the world around them and mathematics, enabling them to search for ways and strategies to solve the proposed problems activating previous knowledge of mathematics, as well as other knowledge. The research was based on a qualitative analysis, situated in the modality of research-teaching supported by theoretical references about Problem Solving. We use as a data collection instrument the application of problem solving contexts in which students seek solutions, working in pairs. We use as audio data recordings the audios of the activities; the narratives of male and female students; and the oral discussions that arose during the socialization of these activities. The final product of our research is presented through a collection of teaching materials aimed at teachers, offering elements that contribute to alleviate students' difficulties in solving mathematical problems involving mainly the multiplication and division of natural numbers. Thus, in the conclusion we reach, we understand that it is important for the teacher to take the Problem Solving methodology to the classroom as a way for students to develop themselves.